From the Georgian Christian Art Treasure: Two New Exhibits of the University of Georgia in Tbilisi - Burchuladze, Nina; Gagoshidze, Giorgi; Maghradze, Ermine (Cultural Arts Research and Development, 2025)
The Medieval Christian art treasures of Georgia are particularly rich in metal artifacts. These works are characterized by a wide typological, technological, iconographic, and stylistic diversity. Their chronology is extensive, and their composition is varied. This group mainly includes chased, engraved, or stamped crosses, icons, and liturgical items made primarily of gold and silver, though occasionally of copper or bronze. While a significant portion of these artifacts has already been studied, numerous examples of metal plastic arts, still unknown, lesser-known, and unstudied, remain in Georgian museums, churches, and private collections. The present article introduces two previously unknown ecclesiastical items made of silver, belonging to the Museum of the University of Georgia: a pendant icon and a reliquary cross, which are noteworthy works from functional, substantive, and artistic perspectives. This article serves as the first publication of these items. It aims to disclose their comprehensive research results and incorporate these artifacts into scientific circulation.